The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1074/jbc.m115.645754
|View full text |Cite
|
Sign up to set email alerts
|

Stress-activated Dendritic Cells (DC) Induce Dual Interleukin (IL)-15- and IL1β-mediated Pathways, Which May Elicit CD4+ Memory T Cells and Interferon (IFN)-stimulated Genes

Abstract: Background: Immunological memory is maintained by antigen-independent tonic stimulation. Results: Stress-treated dendritic cells stimulate IL-15-and IL-1␤-mediated pathways, required for optimum memory T cell induction. Conclusion: Stress agents may be responsible for the persistence of immunological memory, involving an epigenetic mechanism. Significance: Repetitive stress may account for tonic stimulation, which maintains immunological memory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 62 publications
2
16
0
Order By: Relevance
“…7 F ). The data are consistent with the present and previous finding ( 15 ) of optimum memory T cell expression requiring both H (DC-mediated maIL-15) and I (DC-mediated IL-1β) pathways, whereas memory B cells require only the H pathway.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…7 F ). The data are consistent with the present and previous finding ( 15 ) of optimum memory T cell expression requiring both H (DC-mediated maIL-15) and I (DC-mediated IL-1β) pathways, whereas memory B cells require only the H pathway.…”
Section: Resultssupporting
confidence: 93%
“…We have previously demonstrated that maIL-15 and IL-1β are up-regulated in CD11C + splenic DC when BALB/c mice were treated with stress agents and OVA ( 10 ). We hypothesized from our studies with CD4 + T cells ( 15 ) that the homeostatic pathway is driven by interaction between maIL-15DC and IL-15Ra on B cells, whereas the inflammasome pathway is driven by interaction between IL-1 expressed by DC and IL-1R on B cells. Analysis of variance of maIL-15 in splenic CD11C + DC showed significant difference between the stress agent-treated mice without OVA immunization ( F = 3.868, p = 0.021), although separately only alum reached significance ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Supporting this notion, recent data showed that antigen-independent immunological memory could be maintained in CD4 + T cells by repetitive stressors of various kinds (Wang et al, 2015). Therefore, it is possible that T cells can be “educated” in the context of antigen-free chronic stress to exert effects on target organs, including the brain.…”
Section: Adaptive Immunity In Affective Disordersmentioning
confidence: 90%
“…These 2 pathways initiate acquired immune responses, including expansion of T-cell clones and differentiation into effector cells. A third signaling pathway is delivered to T-cells by DCs [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%